Efektivitas Komunikasi Organisasi Dalam Penguatan Potensi Bumdes Pada Pelaksanaan Padat Karya Tunai Desa Di Masa Covid-19 - Erlisa Saraswati; Faisal Nomaini; Kgs. Muhammad Sobri (Jurnal Pemerintahan dan Politik, 2021)
The Covid-19 pandemic is used as a momentum by the government to accelerate the improvement of the village economy by revitalizing the role of BUMDes. It is hoped that the future role of BUMDes can become the basis for national economic recovery. BUMDes are considered able to manage Village Cash for Work (PKTD) activities for productive economic business activities. The problem that occurs is how the village government responds to the implementation of the Village Law, especially the role of communication for village government organizations in order to realize improved performance and rural development based on this law. This study aims to see how the village government responds to the implementation of the Village Law, especially the role of communication of village government organizations in order to realize increased performance and rural development based on this law and to analyze the effectiveness of village government organization communication in implementing BUMDes policies for the implementation of Village Cash for Work during the Covid-19  period. to the village community. The research design used a narrative research design, the research method used was descriptive qualitative. The data collection techniques in this study can use in-depth interviews, observation, and documentation studies. The results showed that all activities carried out during the pandemic in Menang  Raya Village to increase the resilience of residents were not well integrated with the BUMDes Gemilang program in Menang Raya Village. Furthermore, organizational communication in strengthening the potential of BUMDes in Menang Raya Village, Ogan Komering Ilir Regency is effective. In addition, the communication pattern carried out by the Menang Raya Village Government and the BUMDes Gemilang, Menang Raya Village is a communication pattern of informal organizations. Keywords: Effectiveness Of Communication, Organizational Communication Patterns, Village Cash For Work (PKTD), Bumdes, Covid-19 Pandemic.